2018
DOI: 10.1002/jbm.a.36551
|View full text |Cite
|
Sign up to set email alerts
|

Vasculature reconstruction of decellularized liver scaffolds via gelatin‐based re‐endothelialization

Abstract: Decellularized liver scaffolds based liver engineering is a promising approach toward developing functional liver surrogates. However, a major obstacle to long‐term transplantation is the hemocompatibility of the bioengineered liver surrogates. One approach to improve the hemocompatibility of engineered liver surrogates is re‐endothelialization. In the current study, immortalized endothelial cells were perfused for re‐endothelialization of decellularized rat liver scaffolds. When compared to the media‐based pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…No recellularization protocol has achieved the combination of all of these components. Several studies have reported the successful implantation of repopulated decelluarized liver grafts . At 40 days, Yang et al .…”
Section: Livermentioning
confidence: 99%
“…No recellularization protocol has achieved the combination of all of these components. Several studies have reported the successful implantation of repopulated decelluarized liver grafts . At 40 days, Yang et al .…”
Section: Livermentioning
confidence: 99%
“…The association with extracellular matrix components can also increase the efficiency of reendothelization. Recently, immortalized endothelial cells were utilized in a proof-of-concept study that demonstrated that the association with gelatin enhances reendothelization of a decellularized liver scaffold [40]. The attachment of endothelial cells was also improved by conjugation with a biopolymer, REDV-ELP, which was able to increase reendothelization of a rat decellularized liver bioscaffold [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, many complications are related to the decellularization process, including the loss of some native critical components and bioactive molecules. Many studies have investigated how to improve the structural properties of acellular scaffolds through conjugation with crosslinking agents or extracellular matrix (ECM) particles or by improving their functionality with modifying agents that could increase cellular attachment and hemocompatibility, such as CD31, REDV peptide, fibronectin, heparin, and gelatin [80,84,93,[101][102][103][104][105]. One study used mice and pig livers that were partially hepatectomized and maintained a few days in vivo before being harvested and decellularized to generate hepatic acellular scaffolds in an active regenerative state.…”
Section: Bioengineered Liver Scaffolds and Their Transplantationmentioning
confidence: 99%
“…The native liver-derived ECM can be used as an intact scaffold for further orthotropic or heterotopic transplantation [102,107,108]. There are different forms of acellular ECM, including hydrogel, powder, and sheet tissue papers.…”
Section: Bioengineered Liver Scaffolds and Their Transplantationmentioning
confidence: 99%